2018
DOI: 10.1186/s12859-018-2435-4
|View full text |Cite
|
Sign up to set email alerts
|

Single sample scoring of molecular phenotypes

Abstract: BackgroundGene set scoring provides a useful approach for quantifying concordance between sample transcriptomes and selected molecular signatures. Most methods use information from all samples to score an individual sample, leading to unstable scores in small data sets and introducing biases from sample composition (e.g. varying numbers of samples for different cancer subtypes). To address these issues, we have developed a truly single sample scoring method, and associated R/Bioconductor package singscore (htt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
404
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 372 publications
(406 citation statements)
references
References 31 publications
2
404
0
Order By: Relevance
“…Additionally, we showed that context/tissue-specific processes such as epithelial-mesenchymal transition were enriched with highly variable genes, as expected given the diverse changes associated with this phenotypic program (43). We used singscore (35) with stability ranks to enable this analysis, demonstrating that singscore can be used to assess enrichment using any ranked data.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Additionally, we showed that context/tissue-specific processes such as epithelial-mesenchymal transition were enriched with highly variable genes, as expected given the diverse changes associated with this phenotypic program (43). We used singscore (35) with stability ranks to enable this analysis, demonstrating that singscore can be used to assess enrichment using any ranked data.…”
Section: Discussionmentioning
confidence: 59%
“…Our aim was to evaluate enrichment accounting for the prioritisation of stability in our list. We adapted singscore (35) to achieve this and computed stability scores for gene sets derived from gene ontologies and KEGG pathways. Gene sets associated with RNA processing (GO:0006396, GO:0008380), the spliceosome complex (GO:0005681), mRNA metabolic process…”
Section: Functional Composition Of Stable Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…E. Analysis of a genetic signature encompassing genes involved in de novo serine synthesis, one-carbon/folate cycle, and rate-limiting de novo purine biosynthesis pathways (SSP-OC-Purine Signature). mRNA counts from the LAML-TCGA dataset were subset on FLT3-mutant (n = 41) and FLT3 wild-type (n = 100) samples, and the degree of correlation of the signature against FLT3 mRNA expression in each subset was performed using the singscore scoring method (45).…”
Section: Flt3-itd Regulates Global Serine Metabolism and Drives Purinmentioning
confidence: 99%